Oxygen Reduction at Carbon‐Supported Lanthanides: The Role of the B‐Site. Issue 2 (2nd December 2015) - Celorrio, Verónica; Dann, Ellie; Calvillo, Laura; Morgan, David J.; Hall, Simon R.; Fermin, David J.
Abstract: The kinetics of the oxygen reduction reaction (ORR) at carbon‐supported transition‐metal oxides in alkaline solutions is systematically investigated as a function of the nature of the B‐site. The study is focused on LaBO3 (B=Cr, Co, Fe, Mn and Ni) nanoparticles synthesized by using an ionic‐liquid route, offering fine control over phase purity and composition. Activity towards the ORR was compared with the commercial Pt/Etek catalyst. Detailed electrochemical analysis employing a rotating ring‐disk electrode provides conclusive evidence that the carbon support plays an important contribution in the faradaic responses. Decoupling the contribution of the carbon support uncovers that the reactivity of LaMnO3 towards the four‐electron ORR pathway is orders of magnitude higher than that for the other lanthanides. We rationalize these observations in terms of changes in the redox state at the B‐site close to the formal oxygen reduction potential. Abstract : On site : Detailed electrochemical analysis of carbon‐supported lanthanide perovskites reveals that LaMnO3 is orders of magnitude more active towards four‐electron oxygen reduction under alkaline conditions. The origin of the reactivity is linked to changes in the redox state of the Mn III sites.